Edukasi Pemeriksaan Radiologi dan Pengobatan Penyakit Tuberkulosis Paru pada Pemberdayaan dan Kesejahteraan Keluarga Desa Cepiring Timur Kabupaten Kendal - Utami, Lucky Restyanti Wahyu; Prayoga, Aryadiva Nugrahaning; Utami, Rose Malinda Andamari Wahyu; Utomo, Slamet; Afriani, Nur (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
The lack of public knowledge regarding pulmonary tuberculosis can influence the increase in the spread of the disease in Indonesia. So the purpose of this community service activity is to increase the knowledge of mothers empowering the welfare of the family of neighborhood association 08 community association 04 East Cepiring Village, Cepiring District, Kendal Regency, Central Java Province, regarding pulmonary tuberculosis. The education provided is related to radiological examinations to establish the diagnosis and treatment of pulmonary tuberculosis so that it is expected to help reduce the number of incidents of the spread of the disease, especially in Kendal Regency. The stages of community service activities consist of licensing, implementation and reporting. The activity was carried out using the lecture method. Based on the community service activities that have been carried out, the results showed that there was an increase in knowledge related to radiological examinations to confirm the diagnosis of pulmonary tuberculosis by 98% and an increase in knowledge related to the treatment of pulmonary tuberculosis by 98% among mothers, empowering the welfare of families, neighborhood association 08 community association 04 East Cepiring Village, Cepiring District, Kendal Regency, Central Java Province. This increase in knowledge is expected to help reduce the number of people suffering from pulmonary tuberculosis in various regions of Indonesia, especially in Kendal Regency.